The Role of Childhood Victimization on the Severity of Adult Offending among Female Sex Offenders. Issue 6 (18th August 2019) - ten Bensel, Tusty; Gibbs, Benjamin R.; Raptopoulos, Kilby
ABSTRACT: Although males comprise the majority of sex offenders, research has found that females sexually offend similarly to male sex offenders. While male and female sex offenders share commonalities, female sex offenders have higher rates of childhood sexual abuse compared to male sex offenders. In addition, previous research has indicated that childhood abuse can predict adult offending; however, severity of these offenses has not been explored for female sex offenders. Therefore, the purpose of this study was to understand the relationship between previous sexual abuse and the severity of future sexual offending for a sample of convicted female sex offenders ( n = 263) from 1995 to 2017 in a southern state. The data consisted of agency files that included police investigation reports, initial offender and victim statements (prior to conviction), court records, offender personal history questionnaires, offender assessment reports, and criminal histories. We found support for the cycle of violence hypothesis in which those who had a history of prior sexual abuse were more likely to have committed the most severe and violent offenses against a child when compared to female offenders who did not report childhood sexual abuse. Implications are discussed based on our findings.